The Influence of Islamic Jurisprudence on Modern Commercial Law - Abdul Ghoni; Mira Nila Kusuma Dewi; Sandra Dewi; Awaluddin; Yusep Ginanjar (Faculty of Law, Universitas Pekalongan, 2025)
This research aims to analyze the influence of Islamic jurisprudence (fiqh) on the development of modern commercial law, focusing on the principles of Islamic law that contribute to the contemporary legal system, both in Muslim-majority countries and within the framework of international law. Through a qualitative approach with literature studies and normative-comparative analysis, this study explores how the basic concepts in fiqh muamalah, such as the prohibition of usury, the principle of contractual justice, transparency, and the prohibition of gharar, have influenced the formation of legal norms in Islamic banking, Islamic insurance (takaful)), and other financial instruments. The findings show that despite the methodological differences between Islamic law and the Western positive legal system, there are significant common ground that allows the integration of Islamic jurisprudence values into modern commercial legal frameworks. The implications of this study show the importance of understanding across legal systems to create more inclusive, ethical, and sustainable economic regulation globally.